Early Rebleeding after Coiling of Ruptured Cerebral Aneurysms: Incidence, Morbidity, and Risk Factors - Sluzewski, Menno (AJNR Am J Neuroradiol, 2005)
BACKGROUND AND PURPOSE: The purpose of this study was to assess the incidence of early rebleeding after coiling of a ruptured cerebral aneurysm, assess the clinical outcome, and identify risk factors for this event. METHODS: Early rebleedings occurred in 6/431 (1.4%) consecutive patients after coiling of a ruptured aneurysm. Clinical condition at the time of treatment, aneurysm location and size, initial aneurysm occlusion, timing of coiling, and the presence of an adjacent intracerebral hematoma in the six patients with early rebleedings were compared with the remaining 425 patients. RESULTS: Incidence of early rebleeding after coiling of a ruptured aneurysm was 1.4%, and mortality was 100%. Independent risk factors are the presence of an adjacent intracerebral hematoma and small aneurysm size. Dependant risk factors are location on the anterior communicating artery, initial incomplete aneurysm occlusion, and poor clinical condition at the time of treatment. CONCLUSION: Early rebleeding after coiling of ruptured aneurysms is a major concern, in particular because the mortality is very high. A more restricted postembolization anticoagulation strategy in high-risk aneurysms may possibly prevent the occurrence of this devastating event.